The russian-ukrainian crisis: A legal analysis of the conflict in Eastern Europe - Maúrtua de Romaña, Oscar (2022)
The Russian-Ukrainian crisis presents a series of complex approaches to international law that start from the Donetsk and Lugansk declarations of independence and even the use of force to claim territories or to enforce international conventions. The truth is that international law and the Charter of the United Nations seek to prohibit any threat or use of force against the sovereignty and integrity of a State, regardless of the type of controversy, dispute or historical or cultural claim of a territory. These inviolable legal provisions must be analyzed and contrasted with factual facts for a better understanding of the seriousness of this aggression against Ukraine and against international peace and security.